Parent–adolescent communication quality does not moderate the association of emotional burden and somatic complaints in adolescents: a cross-sectional structural equation model - Holger Zapf (Child and Adolescent Psychiatry and Mental Health)
Abstract An explanation for somatic complaints in adolescence assumes that they have the function to express emotional burden if the communication of feelings in important relationships does not work sufficiently. Therefore, it can be hypothesized that in adolescents, lower quality of emotional communication with a parent goes along with a higher impact of emotional burden on somatic complaints. The aim of this study was to examine whether emotional communication quality between adolescents and parents moderates the association of emotional burden and somatic complaints. Based on data from a cross-sectional population sample (N = 1061), structural equation modeling (SEM) was used to test the hypothesis. In addition to the general model, models for boys and girls were compared. Emotional communication quality does not moderate the association of emotional burden and somatic complaints in the general model or in the gender-based models. However, communication quality is a significant predictor of somatic complaints for boys. Limitations are the cross-sectional nature of the data, the possible sampling bias due to the use of an online access panel, and the inclusion of one parent per adolescent. This study highlights that emotional communication quality is a predictor for somatic complaints in adolescent boys and should be addressed in therapy. Trial registration ClinicalTrials.gov: NCT05332236.